x/y=x+y
Multiply by y:
x=xy+y²
Add (x/2)²:
x+x²/4 = y²+xy+x²/4
Factor the right-hand side:
x+x²/4 = (y+x/2)²
Take the square root of both sides:
y+x/2 = ±√(x+x²/4)
Subtract x/2:
y=-x/2±√(x+x²/4)
And we are done.
2006-12-10 13:35:31
·
answer #1
·
answered by Pascal 7
·
0⤊
0⤋
(x / y) = x + y --- Multiply both sides by y to get rid of the initial fraction...
x = y² + yx --- Subtract x from both sides...
y² + xy - x = 0 --- We now have a quadratic equation in general form (ax² + bx + c = 0). We can solve for y using the quadratic formula: x = [-(b) ± â(b² - 4ac)] / 2a. For our purposes, x = y, a = 1, b = x, and c = (-x).
y = [-(x) ± â(x² - 4(1)(x))] / 2(1)
y = [-x ± â(x² - 4x)] / 2
2006-12-10 13:45:31
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
x/y=x+y
Multiply by y:
x=xy+y²
Add (x/2)²:
x+x²/4 = y²+xy+x²/4
Factor the right-hand side:
x+x²/4 = (y+x/2)²
Take the square root of both sides:
y+x/2 = ±â(x+x²/4)
Subtract x/2:
y=-x/2±â(x+x²/4)
2006-12-10 13:36:58
·
answer #3
·
answered by adidasfan90210 2
·
0⤊
0⤋
Okay you could try it this way.
Multiply both sides by y and you get
x = xy+y^2
then subtract xy from both sides to get
y^2 = x-xy
then take the square root of both sides to get y
2006-12-10 13:42:53
·
answer #4
·
answered by anjelfun 4
·
0⤊
0⤋
x/y=(x+y)/1
cross multiply
x=y2+yx
y2+yx-x=0.
i think y can equal anything EXCEPT ZERO, since you can't have zero in the denominator.
2006-12-10 13:38:44
·
answer #5
·
answered by Spearfish 5
·
0⤊
0⤋
x/y = x + y
subtract x from both sides...
x/y - x = x - x + y
x/y - x = 0 + y
x/y - x = y
2006-12-10 13:33:57
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
x/y-x=y
just subtract x from both sides
2006-12-10 13:31:54
·
answer #7
·
answered by asdf77 2
·
1⤊
1⤋